Representative elementary volume determination and heat conduction simulation for porous geomaterials based on CT images - XIE Chuanxi; CHI Ping; XIAO Rong; CHU Zhaoxiang; LI Xiaozhao (矿业科学学报)
Macroscopic thermo-physical properties as well as heat and mass transfer processes in porous geomaterials are significantly affected by mesoscopic solid/fluid composition and pore/particle structure. Given that, a fractal approximate criterion was proposed in the framework of continuum mechanics, aiming to determine the size of the porosity-based geotechnical representative elementary volume (REV). The criterion can be described as follow: the edge length of the cubic porosity REV approximately equals to five times of the maximum pore diameter of the targeted geomaterials. Based on this new criterion, two types of porous geomaterials: sandstone and foamed concrete, were selected, and the sample CT scanning experiments were carried out. Accordingly, the 3D pore structures were reconstructed and analyzed using obtained 2D CT images, based on which the finite element simulation of 1D steady-state heat conduction was then conducted. The results indicate that: (1) the porosity REV is approximately the same size as the thermal conductivity REV; (2) the pore structure of artificial foamed concrete is relatively organized than that of natural sandstone; (3) orders of magnitude discrepancy in thermal conductivity of solid/fluid components and complex pore/particle structure have significant effect on the temperature distribution during heat conduction, which in turn leads to convergence, divergency and turning of conduction heat flow, finally causing variation of the macroscopic effective thermal conductivity (ETC) and resulting in complexity of related research efforts on the prediction of the ETC of tanglesome geomaterimals.